2014
DOI: 10.4049/jimmunol.1303048
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Fibroblasts Induce a Distinct Proinflammatory/Profibrotic Macrophage Phenotype in Pulmonary Hypertension

Abstract: Macrophage accumulation is not only a characteristic hallmark but also a critical component of pulmonary artery (PA) remodeling associated with pulmonary hypertension (PH). However, the cellular and molecular mechanisms that drive vascular macrophage activation and their functional phenotype remain poorly defined. Utilizing multiple levels of in vivo (bovine and rat models of hypoxia-induced PH, together with human tissue samples) and in vitro (primary mouse, rat, and bovine macrophages, human monocytes, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
175
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(185 citation statements)
references
References 69 publications
8
175
0
2
Order By: Relevance
“…Using this model, we identified Arg1 expression in lung granulomas analogous to those in TB patients and in NHP models of TB (11,38). Arg1-expressing cells surrounded the necrotic, hypoxic center of caseous granulomas, suggesting the hypoxic environment in this region potentially contributes to Arg1 induction (39,40,(47)(48)(49). As reported in human and NHP TB granulomas (11,38), inflammatory macrophages were the major cellular population expressing Arg1 in TB lung granulomas of Nos2 −/− mice.…”
Section: Discussionmentioning
confidence: 65%
“…Using this model, we identified Arg1 expression in lung granulomas analogous to those in TB patients and in NHP models of TB (11,38). Arg1-expressing cells surrounded the necrotic, hypoxic center of caseous granulomas, suggesting the hypoxic environment in this region potentially contributes to Arg1 induction (39,40,(47)(48)(49). As reported in human and NHP TB granulomas (11,38), inflammatory macrophages were the major cellular population expressing Arg1 in TB lung granulomas of Nos2 −/− mice.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, microenvironmental signals within the adventitia, in addition to hypoxia, are likely driving the PH-Fib phenotype. In addition, as we have previously shown for inflammatory macrophages, HIF1 signaling can be increased by a variety of factors (e.g., lactate, IL-6 [6,23,36]). However, the exact microenvironmental signals that induce and maintain cellular changes in metabolism remain elusive.…”
Section: Discussionmentioning
confidence: 96%
“…We have documented that, in both experimental hypoxic PH and human PH, the pulmonary artery adventitia harbors activated fibroblasts (hereafter termed PH-Fibs) with a hyperproliferative, apoptosis-resistant, and proinflammatory phenotype, which persists ex vivo over numerous passages in culture (15)(16)(17)(18)(19). Furthermore, in line with the paradigm that stromal cells play a critical role in initiation and perpetuation of vascular inflammation (14,(20)(21)(22), we have recently shown that PH-Fibs potently recruit, retain, and activate naive macrophages through paracrine signaling (17,23). However, at present, no studies have tested the hypothesis that abnormalities in mitochondrial metabolism drive the dramatic phenotypic changes observed in adventitial fibroblasts in PH, and even more importantly, if metabolic alterations can become imprinted and persist ex vivo.…”
mentioning
confidence: 80%
“…Although the activation of STAT3 was first described in Th1 lymphocytes (44), increasing evidence suggests that this pathway plays a major role in Th2 lymphocyte differentiation (45)(46)(47). The Wnt/b-catenin pathway also stimulates Th2 differentiation, as well as IL-4 and IL-13 production, in human CD4 + T cells in a mouse model of allergic asthma (48,49).…”
Section: Discussionmentioning
confidence: 99%